The girls I've been - Sharpe, Tess (New York : Putnam/G.P. Putnam's Sons, 2021)
When seventeen-year-old Nora O'Malley, the daughter of a con artist, is taken hostage in a bank heist, every secret she is keeping close begins to unravel.
Ages 14 up.
Grades 10-12.
Keywords: Swindlers and swindling -- Fiction; Hostages -- Fiction; Bisexuality -- Fiction